The Effect Of Application Of Government Accounting Standards, Implementation Of Internal Control Systems, And Completion Of Audit Findings On The Quality Of Financial Reports With Human Resources Competency As A Moderating Variable. Issue 3 (2023) - Sukma, Aan; Hidayah, Nurul
No abstract available